Non-canonical Targets Mediating the Action of Drugs of Abuse: Cocaine at the Sigma-1 Receptor as an Example - Su, Tsung-Ping (Frontiers in Neuroscience, 2019)
In addition to acting on traditionally recognized receptors or transporters on the plasma membrane, several drugs of abuse, including amphetamine, methamphetamine, nicotine, opioid, cocaine, ketamine, and cannabinoid, have been shown to exert their effects by acting on additional molecular targets either on the plasma membrane or inside a cell. These targets are usually nascent receptors or proteins that can cause downstream signaling or molecular events, leading to altered physiological outcomes favoring addictive processes. However, those “non-canonical” targets of drugs of abuse, in general, have not been widely recognized in drug abuse research. This perspective diverts attention to those underrecognized targets, in the hope of promoting a more complete understanding of the action of drugs of abuse.